Existence of Pentatrichomonas hominis in Tibetan Antelope (Pantholops hodgsonii) - Liu, Shuo; Li, Jing-Hao; Qin, Si-Yuan; Jiang, Jing; Wang, Zhen-Jun; Ma, Tao; Zhu, Jun-Hui; Geng, Hong-Li; Yan, Wei-Lan; Xue, Nian-Yu; Tang, Yan; Sun, He-Ting (Frontiers in Veterinary Science, 2025)
IntroductionPentatrichomonas hominis is a conditional pathogen that parasitizes the intestines of vertebrates and has been detected in various wild animals. However, its infection rate in Tibetan antelopes has not been previously studied.MethodsIn this study, 503 fecal samples from Tibetan antelopes were analyzed to determine the prevalence and molecular characteristics of P. hominis.ResultsResults showed that 1.19% (6/503) of the samples tested positive, and although the prevalence was low, this finding underscores the importance of monitoring wild animals population as hosts of zoonotic pathogens. Additionally, the highest prevalence in Nima County (6.25%, 4/64), followed by Shenza County (2.44%, 2/82). No P. hominis was detected in samples from Shuanghu, Ruoqiang, Qiemo, and Qumarlêb Counties. Seasonally, the highest prevalence was recorded in autumn (1.42%, 6/423). Interestingly, P. hominis was only detected in 2020 (2%, 6/300), with no infections found in 2023 (0/50) or 2024 (0/153). Additionally, the phylogenetic analysis indicated that most islolates belonged to the CC1 genotype, with one representing a potential novel genotype.DiscussionThis is the first s to report the presence of P. hominis in Tibetan antelopes, revealing that Tibetan antelopes may be a potential transmitter of zoontic P. hominis. These findings offer new insights into its epidemiology and contribute valuable data for Tibetan antelope conservation efforts.